Predictors of poor clinical outcome of cryptococcal meningitis in HIV-infected patients - Anekthananon T. (2014)
The aim of this study was to identify baseline prognostic factors for poor clinical outcome of HIV-associated cryptococcal meningitis. We conducted a trial in Thailand and the USA comparing low- and high-dose concomitant use of amphotericin B and fluconazole for HIV-associated cryptococcal meningitis to amphotericin B followed by fluconazole. Subjects who were either alive and cerebrospinal fluid (CSF) culture-positive or dead were considered to have a poor outcome. At day 14, baseline characteristics associated with poor outcome included: low weight, high CSF cryptococcal antigen (CrAg) titre and low CSF white blood cell (WBC) count. At day 70, the associated baseline characteristics included: CSF CrAg titre > 1:1024 and low Karnofsky performance status. Overall, consistent with published findings, low weight, high CSF CrAg titre and low CSF WBC counts at baseline were predictors for poor clinical outcome. In addition, we found that low Karnofsky performance status was predictive of poor outcome. Prompt management with appropriate antifungal therapy for this particular group of patients may improve the outcomes.